Growth Differentiation Factor 15 May Predict Mortality of Peripheral and Coronary Artery Diseases and Correlate with Their Risk Factors - Lung-An Hsu; Semon Wu; Jyh-Ming Jimmy Juang; Fu-Tien Chiang; Ming-Sheng Teng; Jeng-Feng Lin; Hsuan-Li Huang; Yu-Lin Ko (Hindawi Limited, 2017)
Plasma GDF15 concentrations were measured in 612 Taiwanese individuals without overt systemic disease. Clinical parameters, GDF15 genetic variants, and 22 biomarker levels were analyzed. We further enrolled 86 patients with PAD and 481 patients with CAD, who received endovascular intervention and coronary angiography, respectively, to examine the role of GDF15 level in predicting all-cause mortality. Significant associations were found between GDF15 genotypes/haplotypes and GDF15 levels. The circulating GDF15 level was positively associated with age, smoking, hypertension, and diabetes mellitus as well as circulating levels of lipocalin 2 and various biomarkers of inflammation and oxidative stress. Kaplan-Meier survival analysis showed that baseline GDF15 levels of above 3096 pg/mL and 1123 pg/mL were strong predictors of death for patients with PAD and CAD, respectively (P=0.011 and P<0.001). GDF15 more accurately reclassified 17.3% and 29.2% of patients with PAD and CAD, respectively (P=0.0046 and P=0.0197), compared to C-reactive protein. Both genetic and nongenetic factors, including cardiometabolic and inflammatory markers and adipokines, were significantly associated with GDF15 level. A high level of GDF15 was significantly associated with an increase of all-cause mortality in patients with high-risk PAD and in patients with angiographically documented CAD.